2018
DOI: 10.1101/378950
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive analysis of retinal development at single cell resolution identifies NFI factors as essential for mitotic exit and specification of late-born cells

Abstract: Precise temporal control of gene expression in neuronal progenitors is necessary for correct regulation of neurogenesis and cell fate specification. However, the extensive cellular heterogeneity of the developing CNS has posed a major obstacle to identifying the gene regulatory networks that control these processes. To address this, we used single cell RNA-sequencing to profile ten developmental stages encompassing the full course of retinal neurogenesis. This allowed us to comprehensively characterize changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 81 publications
(98 reference statements)
3
29
0
Order By: Relevance
“…Another cluster assigned was AC/HCs exhibited markers for both these fates, like TFAP2B and PTF1A. As previously reported (Clark et al, 2018), while ACs and HCs are distinct fates, it is difficult to separate them by their transcriptomes in early development and without an appropriate amount of sequenced cells for proper resolution.…”
Section: Lhx4 Bac-gfp Transgenic Line Has Gfp Activity In Photoreceptmentioning
confidence: 79%
See 1 more Smart Citation
“…Another cluster assigned was AC/HCs exhibited markers for both these fates, like TFAP2B and PTF1A. As previously reported (Clark et al, 2018), while ACs and HCs are distinct fates, it is difficult to separate them by their transcriptomes in early development and without an appropriate amount of sequenced cells for proper resolution.…”
Section: Lhx4 Bac-gfp Transgenic Line Has Gfp Activity In Photoreceptmentioning
confidence: 79%
“…One other cluster was comprised entirely of cycling cells, exhibiting markers such as OLIG2, NEUROG2, OTX2 and ATOH7, which identify neurogenic RPCs (Cepko, 2014;Clark et al, 2018) as these markers in cycling cells indicate restricted RPCs close to their final division. A second cluster had a fraction of cycling cells, high ATOH7 levels and expression of POU4F2, but no OTX2 or OLIG2, which we assigned to RGC/AC RPCs and Precursors as they exhibit some markers of likely differentiation to RGCs or ACs.…”
Section: Lhx4 Bac-gfp Transgenic Line Has Gfp Activity In Photoreceptmentioning
confidence: 99%
“…Our RNA velocity workflow, which is 13 times faster than velocyto 11 , is suitable for analysis of large datasets that were previously challenging to pre-process. To illustrate this we computed RNA velocity vectors for recently published data from the developing mouse retina 30 consisting 113,917 cells ( Figure 3). We found that six pseudotime marker genes highlighted in the Clark et al 2019 paper 31 (Crx, Nrl, Otx2, Pax6, Rbpms, Rlbp1) displayed patterns consistent with the RNA velocity vectors, and with the pseudotime analysis of Clark et al 31 (Supplementary Figure 8).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that Casz1 regulates the mid/late temporal identity in RPCs. During retinal development, the expression of Casz1 mRNA and protein steadily increases in RPCs, peaks at around P0, and declines postnatally ( Fig 1A) [3,15]. We previously generated a Casz1 conditional knockout (cKO) mouse, and found that Casz1 is required in the retina to suppress the production of early-born neurons and late-born Müller glia, while promoting the production of rod photoreceptors [15].…”
Section: Casz1 Suppresses Müller Glia Production In Postnatal Retinalmentioning
confidence: 99%
“…In regions of the central nervous system (CNS) such as the neocortex and retina, progenitors undergo additional temporal identity transitions in competence to generate specific neuron subtypes at precise stages of development. In the vertebrate retina, retinal progenitor cells (RPCs) have two distinctive phases of multipotency [2][3][4][5]. Within each phase, RPCs can simultaneously produce a number of different neuronal and glial subtypes.…”
Section: Introductionmentioning
confidence: 99%